2019
DOI: 10.4314/ahs.v19i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated management of HIV/NCDs: knowledge, attitudes, and practices of health care workers in Gaborone, Botswana

Abstract: Background: The epidemiologic transition and double disease burden from chronic infections and Non-communicable diseases (NCDs) worldwide requires re-engineering of healthcare delivery systems. Healthcare workers (HCWs) need to adapt to new integrated disease management approaches and change from current disease-specific management. Objectives: The study aimed to determine HCWs knowledge, capacity and skills for management of NCDs among HIV patients and their attitudes towards integrated HIV/NCDs disease manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Progress on the integrated management of HIV and NCDs is continuously reported in the 27 districts, which are PEPFAR supported [2,40,41]. Also, most countries have published research on integrated management of HIV and NCDs, and reported that the research was donor-funded [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Progress on the integrated management of HIV and NCDs is continuously reported in the 27 districts, which are PEPFAR supported [2,40,41]. Also, most countries have published research on integrated management of HIV and NCDs, and reported that the research was donor-funded [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…We developed a semi-structured interview guide, with questions and relevant probes adapted from previous studies [ 12 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ], Appendix 1 . Interviewers were encouraged to attend to emergent themes as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Funding for services, medicines supply and robust research evidence to inform NCD and multi-morbid health policy is still developing (Katende et al, 2015;Manne-Goehler et al, 2016;Price et al, 2018). Conditions such as diabetes and hypertension, and HIV require lifelong care, with integrated care of these conditions garnering increased interest amongst policy makers, scientists and academics in many sub-Saharan African countries (Edwards et al, 2015;Divala et al, 2016;Some et al, 2016;Ameh et al, 2016Ameh et al, , 2017Golovaty et al, 2018;Haldane et al, 2018;Juma et al, 2018;Masupe et al, 2019;Iwelunmor et al, 2019;Kwarisiima et al, 2019;Kintu et al, 2020). Integrated care is defined as "the coordination, colocation or simultaneous delivery of communicable and noncommunicable services to patients who need it, when they need it" (Vorkoper et al, 2019;Singh et al, 2021: p2) and has become a well-received intervention in sub-Saharan Africa when targeting PLHIV and people living with NCDs (Duffy et al, 2017;Singh et al, 2021).…”
Section: Sub-saharan Africamentioning
confidence: 99%